The Influence of Instagram Social Media Use and Hedonistic Lifestyle on the Consumptive Behavior of Female Culinary Arts Education Students, Class of 2023, Universitas Negeri Medan (International Journal of Education and Literature, 2025)
Consumptive behavior among college students has increased along with the development of social media that plays a role in shaping modern lifestyles. This study was conducted to determine the effect of Instagram social media use and hedonistic lifestyle on the consumptive behavior of female students in the Culinary Arts Education Study Program, Universitas Negeri Medan. The study used a quantitative approach with multiple regression analysis methods. Data were obtained by distributing questionnaires to 52 respondents selected using a simple random sampling technique. The results showed that Instagram social media use had a significant effect on consumptive behavior with a significance value of 0.049, while hedonistic lifestyle had a more dominant effect with a significance value of 0.000. Simultaneously, both variables had a positive and significant effect on consumptive behavior with an R² value of 0.418, meaning that 41.8% of the variation in consumptive behavior was explained by these two variables. Based on these results, it was concluded that the higher the use of Instagram social media and hedonistic lifestyle, the greater the tendency of students to behave consumptively.